KNOWLEDGE AND AWARENESS LEVEL OF PREGNANT WOMEN TOWARDS THE IMPORTANCE OF ANTENATAL CARE, IN KSA (CAHIERS MAGELLANES-NS, 2024)
Background: Antenatal care (ANC), according to the World Health Organization, is a general term for services offered to pregnant mothers by qualified birth attendants, The application of ANC depends on personal behavior that shapes knowledge and attitude. Prenatal clinics offer a range of treatments, including risk detection, classification, treatment, and delivery. Therefore, this study intends to evaluate pregnant women's knowledge and awareness of the value of antenatal care in Saudi Arabia.Methodology: A cross-sectional study was conducted with the use questionnaire as a tool to survey data. All pregnant women who participated in KSA with 18 age and over included in the study, The sample size was estimated by using the Qualtrics calculator with a confidence level of 95%; the minimum sample size was 384. The computer's "Microsoft Office Excel Software" (2021) program for Windows was used to input data. Then, to perform statistical analysis, data transmitted to the SPSS application, version 20 (IBM SPSS Statistics for Windows, Version 20.0; Armonk, NY: IBM Corp.). Results: The total sample size was 447 with most participants were aged between 25 to 45 years. As regard awareness level of pregnant women towards the importance of antenatal care, there were 63.5% of the studied participants, exhibited a low level of awareness, while only 27.3% demonstrated a high level of awareness. The remaining 9.2% revealed moderate awareness. Moreover, knowledge score among our participants revealed that 55.9% of them having a high level of knowledge, 33.8% possessing a moderate level of knowledge, and 10.3% exhibiting a low level of knowledge on the subject. As regard relation to sociodemographic characteristics, there was a statistically significant relation to age (p value=0.012), reproductive history (p value=0.005), occupation (p value=0.017), and region of residence (p value=0.003). There was also a statistically insignificant relation to nationality, education level and monthly income. Conclusion: In our study, the majority of the pregnant women had high level of knowledge about the importance of antenatal care. However, the awareness level in some aspects was low. The level of overall knowledge of the respondents about ANC had a significant positive relation to their age, occupation and residence. Thus, health professionals should advocate in increasing community awareness on antenatal care and the possible complications during delivery to decrease the preventable maternal deaths. As the WHO recommendation, starting antenatal care as early as possible in the first trimester and having regular visits to about eight times should be advocated.